Developing a guidance resource for managing delirium in patients with COVID-19. (28th September 2021) - Meagher, David; Adamis, Dimitrios; Timmons, Suzanne; O'Regan, Niamh A; O'Keeffe, Shaun; Kennelly, Sean; Corby, Catherine; Meaney, Anna Maria; Reynolds, Paul; Mohamad, Mas; Glynn, Kevin; O'Sullivan, Roisin
Abstract : As the COVID-19 pandemic escalates worldwide, it is apparent that many patients with more severe illness will also experience delirium. These patients pose a particular challenge in the application of optimal care due to issues with infectious risk, respiratory compromise and potential interactions between medications that can be used to manage delirium with antiviral and other treatments used for COVID-19. We describe a guidance resource adapted from existing guidelines for delirium management that has been tailored to the specific challenge of managing delirium in patients with COVID-19 infection. Issues around the assessment and treatment of these patients are examined and distilled into a simple (one-paged guidance resource that can assist clinicians in managing suspected delirium.